Knowledge, awareness and perception of coronary heart disease (CHD) among residents in Kuantan. - Thandar Soe, Sumaiyah Jamaludin; Jorani, Shuhadah; Saidi, Sanisah (2018)
Introduction: Coronary heart disease (CHD) had been found as the global cause of death of millions of people till now. The lack of knowledge of CHD which consists of its symptoms and risk factors was believed to be the factor of people getting CHD. Objective: This research aimed to determine the level of knowledge, awareness and perception about CHD symptoms and risk factors among residents in Kuantan, Pahang. Methods/ Study Design: A cross sectional study was conducted in Kuantan, Pahang, Malaysia. A total of 400 participants who presented at four shopping malls in Kuantan city were included in this study. A convenient sampling had been used to recruit the subjects from four selected shopping malls. The recruited participants were adult who live in Kuantan, Pahang that aged 18 years old and above, willing to participate, able to read and write. Participants who filled the consent were given a set of validated self-administered questionnaire. Data was analyzed by using SPSS version 22.O. Findings: Majority of the participants were Malays with mean age among 18 to 39 years old. Of the 400 samples, majority had high knowledge of CHD (83.8%), poor awareness (37.3%) and poor perception (35.5%) of CHD. There was an association between age and knowledge, age and awareness level, age and perception, gender and awareness, race and awareness, educational degree and knowledge, and educational degree and perception with p value of less than 0.05 Conclusion: : Residents of Kuantan had poor knowledge, awareness and perception of CHD. Therefore, public health intervention are needed in Kuantan, Pahang to provide knowledge and awareness of coronary heart disease symptoms and risk factors.